(untitled) (Research, Society and Development, 2022)
The literature reveals a possible link between periodontitis and different systemic diseases in companion animals. Faced with this question, it is necessary to understand the factors relevant to this correlation. The objective of this study was to review the literature on the importance of oral health in preventing periodontitis, highlighting the stage of periodontal disease, and its respective impacts on the quality of life and survival of animals, as well clinical signs, diagnosis and treatment of the disease. To this end, an analytical descriptive study was carried out, through bibliographic research, using these digital access platforms such as Capes Periodicals, British Veterinary Association, Research Gate, PubMed, Science Direct, Scielo and BioOne. In light of the literature, it can be seen that periodontitis is a constant potential source of infection and considered a separate risk factor for some cardiovascular, respiratory, endocrine, musculoskeletal and reproductive system-related abnormalities. Depending on the stage of periodontal disease, local and systemic changes may occur. The use of specific foods, toys and toothpastes are efficient forms of prevention. However, daily tooth brushing is the most effective method to remove plaque and maintain the animal’s clinical health. Dentistry is as important as the other existing areas in Veterinary Medicine, being the specialist in this area, the professional capable of correctly treating periodontal disease, which affects signicant numbers of adult dogs and cats.